Antibiotic Lock Therapy with Linezolid for the Treatment of Persistent Catheter-Related Infection in Children with Cancer - Sarı, Neriman; Okur, Nurettin; Çakmakcı, Selma; Aksu, Tekin; İlhan, İnci Ergürhan (Journal of Pediatric Infectious Diseases, 2020)
Objective Central venous catheter (CVC) colonization is a common problem in the pediatric oncology department. Initial colonization of CVC by coagulase-negative staphylococci (CoNS), Staphylococcus aureus, and enterococci is followed by the growth of intraluminal bioﬁlm formation, and results in antibiotic therapy failure. The removal of the old CVC and insertion of new CVC is a difficult and expensive procedure in small children with cancer. The present article aimed to study our treatment results of antibiotic lock therapy (ALT) with linezolid in pediatric cancer patients.Methods This study was planned as retrospective presentation of case series with eight pediatric cancer patients treated with 11 courses of systemic and linezolid lock therapy. Demographic information, clinical findings, laboratory data, blood culture results, complications, and outcome were collected for each patient retrospectively and descriptive statistical methods were used.Results Prior to treatment, peripheral and CVC blood culture results showed Staphylococcus epidermidis in seven patients and Staphylococcushominis in four patients. All pathogens were susceptible to vancomycin and teicoplanin; first-line treatment was vancomycin in six and teicoplanin in five patients. After first-line treatment, peripheral blood cultures of all patients were negative, whereas blood cultures from CVC remained positive. During second-line therapy with linezolid, microbiological eradication was achieved on the fourth day of treatment in each patient. Median catheter survival time for all patients was 14 (range: 8–30) months. No side effects were observed during the treatment and no resistant organisms were documented.Conclusion Although multicentric prospective controlled trials will be required to provide more generalizable results, we suggest that systemic antibiotics combined with linezolid lock therapy used in pediatric cancer patients may be an effective option in treating catheter-related bloodstream infection (CRBSI) and prolonging CVC survival when CoNS are identified.
Keywords: catheter-related blood stream infection; linezolid; antibiotic lock therapy; pediatric cancer patients